Enhancing Cryptographic Resilience through Symmetric Encryption Algorithm Utilizing Variable Length Chromosomes Genetic Algorithm - Ahmed Jobaer; Nur Hafiza Zakaria; Farida Hazwani Mohd Ridzuan; A H Azni (Usim Press, 2026)
Indexed by MyCite